Effect of Hydrogen Exposure on Mechanical and Tribological Behavior of CrxN Coatings Deposited at Different Pressures on IN718; Materials; Vol. 10, iss. 5 - Obrosov A. Aleksey; Sutygina A. N. Alina Nikolaevna; Volinsky A. Alex; Manakhov A. Anton; Weifs S. Sabine; Kashkarov E. B. Egor Borisovich (2017, 2017)
Title screen